A 'circuitry' approach to tolerance charting. (4th August 2014) - Ngoi, B.K.A.; Lee, Y.P
The most critical step in a tolerance chart is to determine the various unknown working dimensions and their corresponding tolerances that are related to a particular blueprint dimension. The required algorithm in doing so in manual tolerance charting is both tedious and time–consuming. This paper presents a simple path tracing model that is used to achieve the above–mentioned. From this model, the unknown working dimensions and their corresponding blueprint dimensions are reduced to a set of linear equations. All the working dimensions can be easily solved by employing the Gauss elimination technique. Next, the tolerances are balanced using a separate mathematical model. As a result, the complete system is capable of solving all the unknown working dimensions involved in a machining process and obtaining their respective optimised tolerances.